The Influence of Competence, Work Discipline, and Work Environment on Employee Performance at the General Secretariat (Setum) of East Java Regional Police (Polda Jatim) - Siswanti, Luluk Erna; Kustiningsih, Nanik; Rahayu, Sri (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to examine the influence of competence, work discipline, and work environment on employee performance at the General Secretariat (Setum) of the East Java Regional Police (Polda Jatim). The study uses a quantitative approach with multiple linear regression analysis to assess the impact of these factors on employee performance. The results show that competence has a significant positive effect on employee performance, as most employees possess strong knowledge and skills related to their work. Work discipline also significantly affects performance, as employees consistently adhere to rules, show punctuality, and are responsible for their tasks. Furthermore, the work environment has a notable influence, with employees reporting strong support from leadership, good communication, and effective collaboration with colleagues. When examined simultaneously, competence, work discipline, and the work environment collectively contribute to improved employee performance at Setum Polda Jatim. These findings suggest that enhancing employee competence through continuous training, reinforcing discipline, and creating a supportive work environment can significantly improve overall performance in the organization.